2010
DOI: 10.1021/mp100298r
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Imaging and Therapy of Brain Cancer Using Theranostic Nanoparticles

Abstract: The past decade has seen momentous development in brain cancer research in terms of novel imaging-assisted surgeries, molecularly targeted drug-based treatment regimens or adjuvant therapies and in our understanding of molecular footprints of initiation and progression of malignancy. However, mortality due to brain cancer has essentially remained unchanged in the last three decades. Thus, paradigm-changing diagnostic and therapeutic reagents are urgently needed. Nanotheranostic platforms are powerful tools for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 78 publications
0
85
0
Order By: Relevance
“…One series of IBD patients reported increasing risks of NMSC, but immunosuppression as a causative factor was not specifically evaluated. 7,8 In contrast, a prospective cohort study did not find an increase in skin cancer incidence in patients with ulcerative colitis. 9 More recent epidemiological studies continue to report contradictory results: Long and colleagues found that recent and ongoing exposure to thiopurines was associated with increased risk of NMSC, 10 while a Dutch study of 2887 patients reported that thiopurine use was not associated with increased risk of NMSC.…”
mentioning
confidence: 88%
“…One series of IBD patients reported increasing risks of NMSC, but immunosuppression as a causative factor was not specifically evaluated. 7,8 In contrast, a prospective cohort study did not find an increase in skin cancer incidence in patients with ulcerative colitis. 9 More recent epidemiological studies continue to report contradictory results: Long and colleagues found that recent and ongoing exposure to thiopurines was associated with increased risk of NMSC, 10 while a Dutch study of 2887 patients reported that thiopurine use was not associated with increased risk of NMSC.…”
mentioning
confidence: 88%
“…Nanoparticle size and the nature and number of linkers on the NP surface can be optimized to control not only both the loading and the release of the entrapped or covalently linked drug components, but also the crossing through the BBB [114]. DDS can also deliver contrast agents in effective concentrations to the brain, improving the efficacy of existing CNS imaging and treatment regimens [115].…”
Section: C) Drug Delivery Systemsmentioning
confidence: 99%
“…In this case, the properties of nanomaterials may offer solutions to this drawback. The best treatment for brain tumor-targeted drug delivery should be able to transport the therapeutic agents at the brain tumor foci minimizing the involvement of healthy brain tissue as well as of peripheral tissues [115,193].…”
Section: Non-invasive Approachesmentioning
confidence: 99%
“…Indeed, as the development and validation of the world's first (Waehler et al, 2007;Gordon and Hall, 2010), but no longer only (see Reximmune-C; Gordon et al, , 2008, tumortargeted genetic medicine is recognized, the promise and potential of the platform have begun to percolate into the general medical literature, impacting the practice of clinical oncology (Hughes, 2009), medical imaging (Bjojani et al, 2010), medicinal nanotechnology (Peach et al, 2009), and gene therapy (Sverdlov, 2009), as well as the discussions of bedside bioethics (Toh, 2011) and the practical applications of tumor immunology (Zolnik et al, 2010). Looking forward into the future, it is only a matter of time (see Gordon and Hall, 2009) when the progression of metastatic disease is no longer considered to be intractable, and the poor prognosis of chemotherapy-resistant cancer is summarily improved.…”
Section: Looking Back and Then Forward -Reflections On Proper Values mentioning
confidence: 99%